2021
DOI: 10.1186/s12905-021-01439-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bacterial uropathogens and their antimicrobial susceptibility patterns among pregnant women in Eastern Ethiopia: hospital-based cross-sectional study

Abstract: Background Urinary tract infection (UTI) is the commonest bacterial infections during pregnancy, leading to significant maternal and prenatal morbidity and mortality. Method This hospital-based cross-sectional study during November 2017 to January 2018 was aimed to determine hospital-based antibacterial susceptibility patterns of bacterial uropathogens among 200 pregnant women in Eastern Ethiopia. ~ 10–20 ml clean-catch midstream urine samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
(76 reference statements)
1
16
0
Order By: Relevance
“…E. coli was the most frequent etiological agent of UTI, accounting for up to 37.6% of isolated cases. This finding is in agreement with the findings from Ethiopia, 35.7% 31 , Nigeria, 34.2% 32 and India, 37.3% 33 . The possible explanation for this high isolation rate of E. coli in the present finding could be due to the significant abundance of E. coli in the rectal area, which in turn via contamination ascends through genitalia to the urinary tract and causes UTI and it could also be due to E. coli having various enhanced virulence factors specific for colonization and invasion of the urinary epithelium, such as P-fimbriae and S-fimbriae adherence factors which mediate the attachment of E. coli to viginal and uroepithelial cells 34 .…”
Section: Discussionsupporting
confidence: 93%
“…E. coli was the most frequent etiological agent of UTI, accounting for up to 37.6% of isolated cases. This finding is in agreement with the findings from Ethiopia, 35.7% 31 , Nigeria, 34.2% 32 and India, 37.3% 33 . The possible explanation for this high isolation rate of E. coli in the present finding could be due to the significant abundance of E. coli in the rectal area, which in turn via contamination ascends through genitalia to the urinary tract and causes UTI and it could also be due to E. coli having various enhanced virulence factors specific for colonization and invasion of the urinary epithelium, such as P-fimbriae and S-fimbriae adherence factors which mediate the attachment of E. coli to viginal and uroepithelial cells 34 .…”
Section: Discussionsupporting
confidence: 93%
“…experience two or more episodes annually. 12,[17][18][19] Owing to less concern regarding hygiene, old adults (>65 years) had the highest incidence, followed by young adults. 20 Therefore, UTIs complicate the daily lives of people of all ages, notably middle-aged adult women and the oldadult population.…”
mentioning
confidence: 99%
“…1 A most recent study conducted by Ejerssa and companions (2021) reported that >70% of uropathogens were sensitive to gentamicin, chloramphenicol, amikacin and nitrofurantoin. 14 The findings of a study performed by Patel and coworkers (2021) highlighted that among the gram negative pathogens, most resistant drug was ciprofloxacin (95.12 percent), followed by cefipime (87.80 percent), piperacillin-tazobactem, meropenam, (85.37 percent). 12 Increase in antibiotic resistance among uropathogens demonstrates that these are nosocomial infections and therefore complicated to treat.…”
Section: Discussionmentioning
confidence: 99%
“…13 The emergence of antibiotic resistance among urinary pathogens has been increasing worldwide and it becomes an important global public health problem especially among emerging countries. 14 For urinary tract infection, a most favorable treatment requires knowledge regarding local epidemiology as well as antimicrobial susceptibility profiles. Resistance mechanisms have been developed by uropathogens to frequently prescribed antibiotics that limits treatment alternatives of successful therapies.…”
Section: Introductionmentioning
confidence: 99%